SISTEM PENILAIAN KINERJA KARYAWAN PT. CAHAYA IQRA MANDIRI MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Sarwindah, Sarwindah; Marini, Marini (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2019)
In everyday life, humans often encounter problems in decision making, where problems that arise can be large or small, which are very influential in the results of decisions. Now humans are developing systems that can help determine the best alternative in a problem, namely the decision support system (DSS) in the decision support system there are alternatives, criteria and weights used to determine the best solution. The quality of human resources is one of the supporting factors to improve the performance productivity of an agency. So, from that competent human resources can support the level of performance, with performance appraisal, it will be known the achievements of each employee, this can be used by agencies as a consideration in determining the best employees. The purpose of this study is to create a good decision support system that can assist managers in evaluating the performance of an employee in an agency. Judging from the problem of the performance appraisal of an employee at PT. Cahaya iqra Mandiri is the object of research that produces the desired answer, the Admin section is a priority and can be implemented to determine neat administration and have important responsibilities in PT. cahaya iqra Mandiri.